Okun's Law, Development, and Demographics : Differences in the Cyclical Sensitivities of Unemployment Across Economy and Worker Groups - An, Zidong (IMF Working Papers; Working Paper, 2021)
The negative and stable relationship between an economy's aggregate demand conditions and overall unemployment is well-documented. We show that there is a large degree of heterogeneity in the cyclical sensitivities of unemployment across worker and economy groups. First, unemployment is more than twice as sensitive to aggregate demand in advanced as in emerging market and developing economies. Second, youth's unemployment is twice as sensitive as that of adults'. Third, women's unemployment is significantly less sensitive to demand than men's in advanced economies. These findings point to the highly unequal impacts of the business cycle across worker and economy groups.